"Just" blood donors? A study on the multi-affiliations of blood donors. Issue 4 (August 2017) - Alfieri, Sara; Pozzi, Maura; Marta, Elena; Saturni, Vincenzo; Aresi, Giovanni; Guiddi, Paolo
Abstract: Background: The present work proposes to explore a phenomenon well known in the world of blood donation, but little explored by literature: multi-affiliations. By that term, in this paper we mean blood donors' engagement in multiple associations of various natures (donation, recreation, sports, etc.) simultaneously. The first objective proposes to explore the phenomenon of multi-affiliations in descriptive terms; the second is to look into the differences—in terms of motivations, family-work-volunteerism reconciliation, life satisfaction, and membership satisfaction—between those who "only" carry out blood donation activity and those who instead participate in multiple associative realities concurrently. Method: Participating in the research were 2674 donors from the Italian Association of Blood Donors (AVIS) (age range 18–65; 66.6% male) to which a self-report questionnaire was administered in the waiting rooms of numerous blood donation centers. Results: Regarding the first objective, it emerged that only 35.9% of the participants "only" donate blood, while a good 64.1% is engaged also in other associations. Regarding the second objective, statistically significant differences emerge regarding many of the variables considered: social, values, ego-protection, and career motivation; capacity to reconcile family-volunteering and work-volunteering; life satisfaction; and membership satisfaction. Conclusions: The study offers precious information to the agencies that handle recruiting and retaining of donors. The agencies in fact can take away information on how to improve the multi-affiliations of their donors, an aspect that can facilitate their long-term retention.